Long-term impact of organic and conventional farming on soil physical properties under rice (Oryza sativa)-wheat (Triticum aestivum) cropping system in north-western Indo-Gangetic plains - KAJE, V V; SHARMA, D K; SHIVAY, Y S; JAT, S L; BHATIA, A; PURAKAYASTHA, T J; BANDYOPADHYAY, K K; BHATTACHARYYA, RANJAN (The Indian Journal of Agricultural Sciences, 2023)
Long-term (13 years) impact of organic and conventional farming on soil physical properties was evaluated under a rice (Oryza sativa L.) – wheat (Triticum aestivum L.) cropping system in a sandy clay loam soil at New Delhi. The treatments included unfertilized control (T1), conventionally managed (T2) and five organic treatments (T3: FYM @ 10 t/ha to rice and wheat, T4: SGM for rice and LGLM for wheat, T5: SGM + BGA for rice and LGLM + Azotobacter for wheat, T6: SGM + FYM for rice and LGLM + FYM for wheat, and T7: SGM + FYM + BGA for rice and LGLM + FYM + Azotobacter for wheat). The application of organic amendments had positive influence on soil physical properties such as saturated hydraulic conductivity (Ks), field capacity (FC) and permanent wilting point (PWP), plant-available water capacity (PAWC), water holding capacity (WHC), distribution of aggregate size fractions, bulk density (Db), and porosity in the 0-15 and 15-30 cm soil layer. A favourable effect of organic amendments was also found on soil strength (at depth 0-70 cm). Even, values related to these properties were significantly affected by the kinds of organic amendments. But, T1 and T2 had no improvement in soil physical properties over the organic ones. Value of Ks decreased with increase in soil depths. T7 and T3 were superior in Ks to other treatments for 0-15 and 15-30 cm soil depths. Volumetric moisture content at FC (θFC) and PWP (θWP) increased with addition of organic amendments and got varying response due to the kinds of organic amendments or their combinations. θFC and θWP were decreased substantially under T1 and T2, because of no addition of organic inputs. As a result of θFC and θWP, PAWC had also signified an improvement under the influence of different organic amendments over T1 and T2. Generally (for both depths), PAWC of T3, T6 and T7 were 17-26% more than T1, T2, T4 and T5. WHC of upper soil layer (0-15 cm) was greater for organic amended plots than plots devoid of organic inputs and lower values were recorded for 15-30 cm soil layer. WHC of T3, T7 and T6 was highest in comparison to plots amended only with (without FYM) green manure, BGA or Azotobacter as well as T1 and T2 for both depths (0-15 and 15-30 cm). A better soil aggregation was observed under organic amended plots for large and small macro-aggregates (LM - >2 and SM-0.25-2 mm) in both soil depths. Lowest value of Db with highest percentage of pore space was noted under T7 than other treatments in both soil layers. Soil strength was significantly lower in organic amended plots than T1 and T2. This study clearly indicated that application of organic inputs especially FYM, improved the soil physical properties, which resulted in better soil aggregation, porosity and soil moisture retention.